Designing and Molecular Modeling Studies on Novel Bisindole-imidazopyridine Against Adrenocarcinoma - MOURYA, AMAN; kapoor, kapish (Journal of Drug Delivery and Therapeutics, 2019)
Adrenocarcinoma is an uncontrolled growth of epithelial cells originating in the ducts or breast lobules. EGFR or Epidermal growth factor receptor is a transmembrane protein with cytoplasmic kinase activity that transduces important growth factor signaling from the extracellular milieu to the cell. 45 bisindole-imdazopyridine analogues were obtained from the literature. Free-wilson QSAR studies were erformed on the given data set. Compounds were designed on the basis of QSAR studies. Further, Molecular docking studies were performed on the designed compounds to check the binding affinity on the protein. After that Drug-likeliness and ADMET studies were performed on the selected molecules. The results revealed that the selected analogues can be used against the treatment of adrenocarcinoma. Keywords: Adrenocarcinoma, bisindole-imidazopyridine, QSAR, Molecular Docking, ADME studies.